2007
DOI: 10.1128/jb.00966-07
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-Sensing Regulation of the Production of Blp Bacteriocins in Streptococcus thermophilus

Abstract: The blp gene cluster identified in the genome sequences of Streptococcus thermophilus (blp St ) LMG18311, CNRZ1066, and LMD-9 displays all the characteristics of a class II bacteriocin locus. In the present study, we showed that the blp St locus is only fully functional in strain LMD-9 and regulates the production of antimicrobial peptides that inhibit strains LMG18311 and CNRZ1066. The blp St cluster of LMD-9 contains 23 genes that are transcriptionally organized in six operons: blpABC St (peptide transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
113
2
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 49 publications
6
113
2
9
Order By: Relevance
“…For general molecular biology techniques, we followed methods reported previously by Sambrook et al (44). The preparation of S. thermophilus chromosomal DNA and the electrotransformation of E. coli and S. thermophilus were performed as previously described (10,13,15). The primers used in this study were purchased from Eurogentec (Seraing, Belgium) and are listed in Table S1 in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For general molecular biology techniques, we followed methods reported previously by Sambrook et al (44). The preparation of S. thermophilus chromosomal DNA and the electrotransformation of E. coli and S. thermophilus were performed as previously described (10,13,15). The primers used in this study were purchased from Eurogentec (Seraing, Belgium) and are listed in Table S1 in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting PCR fragment was restricted by NcoI, ligated, and transformed into E. coli EC1000. The induction of the promoter P blpU was achieved by the addition of 250 ng ml Ϫ1 D9C-30 synthetic peptide to the cultures at the beginning of growth, as reported previously (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in all three strains the blp locus was also shown to contain genes encoding for a three-component quorum sensing (QS) system, with blpH and blpR encoding a putative histidine kinase and response regulator respectively, and blpC encoding the precursor of the quorum sensing induction peptide (QSIP) (Hols et al, 2005). Overexpression of BlpC in S. thermophilus LMD-9 resulted in the identification of a 30-mer secreted peptide (3403.7 Da) representing the mature pheromone, that plays a key role in the display of bacteriocin activity (Fontaine et al, 2007). Production of an active bacteriocin could also be induced in strain LMD-9 when the 30-mer peptide was added to early log phase cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Production of an active bacteriocin could also be induced in strain LMD-9 when the 30-mer peptide was added to early log phase cultures. However, overexpression of BlpC or extracellular addition of the synthetic peptide had no effect on bacteriocin production in S. thermophilus strains CNRZ1066 and LMG18311 due to mutations in blpB which encodes BlpB, an accessory transport protein required for secretion of the QSIP and bacteriocin peptides (Fontaine et al, 2007). Further analysis of the blp locus in strain LMD-9 showed that expression of BlpD alone was sufficient to inhibit the growth of most target bacteria, but the overall broad spectrum of activity may require expression of multiple peptides (BlpD, U, E, F) and the presence of a thiol-disulfide oxidase encoded by blpG (Fontaine & Hols, 2008).…”
Section: Introductionmentioning
confidence: 99%